Disadvantaged Areas and Educational Inspectorate: A Work Experience in the Polígono Sur Neighborhood of Seville, 2019–2024 - Bermudo del Pino, Rafael (Avances en Supervisión Educativa, 2025)
Spain is home to a large number of socially deprived areas in which a fair share of the academic population needs educational support. Public or political debate rarely takes interest in these disadvantaged groups of students, and their situation is seldom addressed by those in charge of educational policies. As a consequence, school failure, school dropout, and school segregation keep being common among these underprivileged communities. This article describes the work and experiences of two school inspectors based in one of Spain's poorest and most marginalized urban areas: Seville's Polígono Sur.
Keywords: Experience of Education Inspectorate; Compensatory education; School inspection experiences; Social and educational vulnerability; School segregation